Advances in computational intelligence systems : contributions presented at the 17th UK Workshop on Computational Intelligence, September 6-8, 2017, Cardiff, UK /: contributions presented at the 17th UK Workshop on Computational Intelligence, September 6-8, 2017, Cardiff, UK. ([2018]) - Unknown
No abstract available